If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 + -7m + 10 + -3m = 0 Reorder the terms: 30 + 10 + -7m + -3m = 0 Combine like terms: 30 + 10 = 40 40 + -7m + -3m = 0 Combine like terms: -7m + -3m = -10m 40 + -10m = 0 Solving 40 + -10m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + -10m = 0 + -40 Combine like terms: 40 + -40 = 0 0 + -10m = 0 + -40 -10m = 0 + -40 Combine like terms: 0 + -40 = -40 -10m = -40 Divide each side by '-10'. m = 4 Simplifying m = 4
| 2x+2*2x+7=2x+7 | | -21-9h= | | (X+28)=(3x+14) | | 260-64-9= | | (2/7)÷N=(5/7) | | 9.8k+3.7=-0.22 | | a^2-4a+4-b^2= | | y=3e^5x | | 3/4(x-6)=2/8(x+2) | | y^2-16x-64=0 | | 38*x^3+19x^2-158=0 | | R=D-TforD | | .5x-2=.3x+1.2 | | -4c+3-6c=34 | | -x+4x=40 | | 2log(x-5)=6 | | Z/12=12/4 | | X/12=59/60 | | y=-3x^2-6(3)-5 | | 3/w=18/42 | | x^2+4m-12=0 | | N-3=20/8 | | 6x+2=4-(2x-5) | | n^3-n^2=6n | | 4-5+7-4k=0 | | x+16=2x-24 | | 5t-3t=18+3(1-t) | | 2xy=x-3y | | 16-w=72 | | 7+3k-2=4 | | 3x-15=41-5x | | 5n+9-16+4=5(4n-2n+8) |